Dual CCNE1/PIK3CA targeting is synergistic in CCNE1-amplified/PIK3CA-mutated uterine serous carcinomas in vitro and in vivo - Emiliano Cocco; Salvatore Lopez; Jonathan Black; Stefania Bellone; Elena Bonazzoli; Federica Predolini; Francesca Ferrari; Carlton L. Schwab; Gulden Menderes; Luca Zammataro; Natália Buza; Pei Hui; et al. (2016)
Clinical options for patients harbouring advanced/recurrent uterine serous carcinoma (USC), an aggressive variant of endometrial tumour, are very limited. Next-generation sequencing (NGS) data recently demonstrated that cyclin E1 (CCNE1) gene amplification and pik3ca driver mutations are common in USC and may therefore represent ideal therapeutic targets. Cyclin E1 expression was evaluated by immunohistochemistry (IHC) on 95 USCs. The efficacy of the cyclin-dependent kinase 2/9 inhibitor CYC065 was assessed on multiple primary USC cell lines with or without CCNE1 amplification. Cell-cycle analyses and knockdown experiments were performed to assess CYC065 targeting specificity. Finally, the in vitro and in vivo activity of CYC065, Taselisib (a PIK3CA inhibitor) and their combinations was tested on USC xenografts derived from CCNE1-amplified/pik3ca-mutated USCs. We found that 89.5% of the USCs expressed CCNE1. CYC065 blocked cells in the G1 phase of the cell cycle and inhibited cell growth specifically in CCNE1-overexpressing USCs. Cyclin E1 knockdown conferred increased resistance to CYC065, whereas CYC065 treatment of xenografts derived from CCNE1-amplified USCs significantly reduced tumour growth. The combination of CYC065 and Taselisib demonstrated synergistic effect in vitro and was significantly more effective than single-agent treatment in decreasing tumour growth in xenografts of CCNE1-amplified/pik3ca-mutated USCs. Dual CCNE1/PIK3CA blockade may represent a novel therapeutic option for USC patients harbouring recurrent CCNE1-amplified/pi3kca-mutated tumours.